IMPROVING THE STUDENTS’ READING COMPREHENSION THROUGH EXPLICIT TEACHING STRATEGY - Nur Qalby (EXPOSURE : JURNAL PENDIDIKAN BAHASA INGGRIS, 2014)
This research aimed at explaining the improvement  of the  students’ reading comprehension focused on identifying the main idea and getting detail at SMP Negeri 33 Makassar. To explain the improvement, the researcher used a classroom action research  (CAR)  which was  conducted in  two cycles  in which every cycle consisted of four meetings. The location of this research was taken from the second-grade student of SMP Negeri 33 Makassar with the number of the subject i.e. 30 students which consisted 14 men and 16 women. Based on the text above the research findings indicated that the use of Explicit Teaching Strategy was significant in improving the students’ reading comprehension which focused on identifying the main idea and getting detail. It was proved by the mean score of Diagnostic Test was 4.94 that classified poor. The improvement in Cycle I was 6.11 that classified fair and Cycle II was 7.26 that classified fairly good. While the standard target achievement was 6.5, it means that the standard target achievement had been achieved.Keywords: reading comprehension, main idea, classroom action research